입원 시 배우자 지지 강화 출산교육이 산부와 배우자의 분만자기효능감 및 분만경험지각에 미치는 효과 - 엄소예; 김은실; 김현정; 방양옥; 전나미; Eom, So-Ye; Kim, Eun-Sil; Kim, Hyun-Jung; Bang, Yang-Ok; Chun, Na-Mi (Journal of Korean Academy of Nursing, 2012)
Purpose: This study was conducted to evaluate the effect of a one-session spouse-support enhancement childbirth education on childbirth selfcefficacy and perception of childbirth experience. Methods: The design of this study was a nonequivalent control group pretest-posttest experiment. The participants in the study were 31 couples in the experimental group and 30 in the control group. The experimental couples were provided with one session on spouse-support enhancement childbirth education the night before delivery. Data were collected at two hours after delivery using the Childbirth Self-Efficacy Inventory (CBSEI) and perception of childbirth experience scale. Data were analyzed using PASW statistics 18 program. Frequencies, percentage, mean, $x^2test$, t-test were used for data analysis. Results: Childbirth self-efficacy significantly increased in the experimental group as compared to the control group, but there was no significant difference in perception of childbirth experience in the experimental group compared to the control group. Conclusion: The results suggest that a one-session childbirth education has beneficial effects on enhancing childbirth self-efficacy in pregnant couples. A one-session spouse-support enhancement childbirth education is recommended as an effective nursing intervention to promote couple's childbirth self-efficacy and it is also recommended that modifications of program to promote women's childbirth experience should be considered.